THE ROLE OF CHATGPT IN ENHANCING ENGLISH LANGUAGE SKILLS: A SYSTEMATIC REVIEW - Siti Kholida Ziya Ar-Rahmah; Alfina Husna Azkia; Nafan Tarihoran (Adisam Publisher, 2025)
This research aims to analyze the role of ChatGPT in improving English language skills through systematic literature review. The method used is a systematic analysis of 43 journals related to ChatGPT and English education obtained from Mendeley, with a focus on the benefits, challenges, and pedagogical implications of using AI in language learning. Research results show that ChatGPT provides benefits in the development of writing and speaking skills through interactive feedback, AI-based exercises, and conversation simulations that allow students to practice in real contexts. In addition, ChatGPT supports independent learning, increases student involvement, enriches vocabulary, and helps in formative assessment by providing corrections and improvement suggestions. However, this study also found significant challenges, including excessive reliance on technology, lack of understanding of cultural context, potential bias in AI response, as well as the risk of plagiarism and academic integrity violations. In addition, the quality of the answers produced is not always accurate, so teacher guidance is needed to ensure that students continue to think critically and not just passively receive information. In conclusion, although Chat GPT has transformational potential in English learning, its effectiveness is highly dependent on ethical implementation, appropriate pedagogical strategies, and clear regulations. Therefore, training is needed for educators to optimize its use in learning, as well as a blended learning-based approach that combines AI technology with direct interaction between teachers and students to create a balanced, effective, and appropriate learning environment for the needs of learners.